Body Image, Dietary Intake, and Nutrition Knowledge in Relation to Body Composition in Ballerinas - Muslimatun, Siti; Alianto, Daniel Christopher; Bewintara, Emilia; Harjadi, Kenn Rafael (Jurnal Gizi dan Pangan, 2023)
Body composition in relation to body image, dietary intake, and nutrition knowledge among ballerinas were assessed in this study. This cross-sectional study collected data from ballet schools in Jakarta and Bekasi using anthropometric measurements and interviews. Among participants aged 8‒39 years, more than 50% had normal range body composition, 65.4% had self-perceived negative body image, more than 71% had normal dietary intake; however, 67.3% had low nutrition knowledge score. Overweight ballerinas had significantly higher body fat, fat-free mass, fat-free mass index and muscle mass index, except for total-body-water (p<0.05). There is correlation between body composition and body image among ballerinas resided in Jakarta and Bekasi.